2000
DOI: 10.1017/s0950268800004726
|View full text |Cite
|
Sign up to set email alerts
|

Serological and virological evidence of non-sexual transmission of human herpesvirus type 8 (HHV8)

Abstract: To evaluate whether or not human herpesvirus 8 (HHV8) can be transmitted through a non-sexual route a serological survey was carried out in a group of 51 catholic nuns. The seroprevalence rate and the geometrical mean antibody titre to anti-latent HHV8 antigen were similar in nuns and in a group of 60 women, matched by age, in the general population (27 vs. 24%; 1028 vs. 1575, respectively). Moreover, by using nested polymerase chain reaction (PCR), HHV8 DNA sequences were detected in 7 of 16 (43.8%) saliva an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 16 publications
2
36
0
1
Order By: Relevance
“…Both the close family members and heterosexual partners of KS patients show increased KSHV seroprevalence (19,56), while a group of 51 Catholic nuns in Italy had a seroprevalence indistinguishable from that of matched female controls (517). Similar to AIDS-associated KS patients, the high frequency of detection of KSHV DNA in tonsillar swabs from HIV-negative KS patients in Italy suggests that transmission in saliva is a predominant route (75).…”
Section: Classic Ksmentioning
confidence: 99%
“…Both the close family members and heterosexual partners of KS patients show increased KSHV seroprevalence (19,56), while a group of 51 Catholic nuns in Italy had a seroprevalence indistinguishable from that of matched female controls (517). Similar to AIDS-associated KS patients, the high frequency of detection of KSHV DNA in tonsillar swabs from HIV-negative KS patients in Italy suggests that transmission in saliva is a predominant route (75).…”
Section: Classic Ksmentioning
confidence: 99%
“…Seroepidemiological studies have shown high prevalence rates of HHV-8 antibodies among male homosexuals (1-3), African children (4,5), Brazilian Amerindians (6) and elderly individuals in certain regions of Europe (3,7). However, there is no single route of transmission explaining how the virus can infect such different population groups.…”
mentioning
confidence: 99%
“…In one study, it was reported that the detection rate of KSHV DNA in PBMC was 16.5% in 158 healthy KSHV-seropositive adults (Brown et al, 2005). In another work, the KSHV DNA in PBMC was detected only in one person out of 12 KSHV-seropositive healthy individuals (Vitale et al, 2000). Further analysis of the risk factors associated with KSHV indicated that KSHV infection was associated with advancing age, low education level, and stationary population status.…”
Section: Discussionmentioning
confidence: 99%